ANALYSIS OF THE SCIENTIFIC PRODUCTION OF ACADEMIC SELF-REGULATION LEARNING IN THE EDUCATIONAL CONTEXT - Lima Fluminhan, Carmem Silvia [UNESP]; Murgo, Camelia Santina (Centro Univ Nove Julho, 2020)
The objective of this research is to present and discuss how self-regulated learning has been investigated in the educational context through the examination of scientific publications produced up to June 2016 and available on online databases. The analysis of the 20 publications obtained for this investigation allowed to identify that self-regulated academic learning has been predominantly studied through the Cognitive Social Theory theoretical approach. The empirical studies, of qualitative approach, at higher education level, with evaluative objective, and in article format were prevalent. Moreover, the reported studies converged to the understanding that self-regulated learners demonstrate to have more than cognitive strategies, they indicate to bear motivational skills. Considering the results obtained, it is suggested that self-regulated academic learning be a topic of continuous study, supported by educational institutions and by teachers, aiming to develop and strengthen the three self-regulatory dimensions in students: metacognitive, motivational and behavioral.
Keywords: Academic self-regulation; Education; Scientific publication; Social cognitive theory; Teaching and learning